L’Edizione nazionale dei Quaderni del carcere - Giuseppe Cospito (Laboratoire Italien)
Gramsci’s prison manuscripts were published, first in a partial form according to subject matter, by Felice Platone and then, in a complete form in chronological order by Valentino Gerratana, with the exception of the translations that Gramsci did between 1929 and 1932. Beginning with L’officina gramsciana (The Gramscian Workshop), Gianni Francioni has carried forward and corrected the work of philological restoration undertaken by Gerratana, arriving at a formulation of the basic criteria for a new publication of the Prison Notebooks within the context of the National Edition of Gramsci’s writings. The first volume of the National Edition came out in 2007 and included the Translation Notebooks, of interest for the nexus that emerges with the theoretical notes. The second and third volume, currently underway, will be deal with the miscellaneous notebooks and the “special” ones, arranged in order of writing according to the new chronology that Francioni has established, contained here as an appendix.